Scheduling Analysis using CPM, PERT, and LoB Method - Milinda Nur Indah Puspita; I Nyoman Dita Pahang Putra (Sustainable Civil Building Management and Engineering Journal, 2026)
Project delays frequently occur in construction projects and often result from the inability to accurately identify critical activities within the project network, leading to ineffective time control. Therefore, it is necessary to apply scheduling methods that are appropriate to the characteristics of the project in order to improve time control effectiveness and minimize the risk of delays. The aim of this research is to analyze scheduling results using the Critical Path Method, Program Evaluation and Review Technique, and Line Of Balance method. Also, to determine the difference in project completion duration using the PERT, CPM and LoB Methods. This research employs a quantitative method with a comparative approach, using secondary data that was obtained from a supervisory consultant. The data includes the durations and the work list. The analysis data is obtained to determine the critical path using PERT, CPM and LoB methods. The PERT method calculates three estimation times: optimistic duration, most likely duration, and pessimistic duration to determine the critical path. The results show the CPM and LoB method predicts the completion project in 159 days, and the PERT method predicts the completion project in 164 days. The difference in completing the project using the CMP and PERT methods is 5 days. The difference in project completion duration between LOB and PERT is 5 days. In contrast, no difference is observed between the CPM and LOB methods, as both yield an identical project completion time of 159 days.